MgO nanoparticles-decorated carbon fibers hybrid for improving thermal conductive and electrical insulating properties of Nylon 6 composite. (18th August 2017) - Zhang, Jingxin; Du, Zhongjie; Zou, Wei; Li, Hangquan; Zhang, Chen
Abstract: A magnesium oxide (MgO) nanoparticles-decorated carbon fiber hybrid (CFMgO) were designed and fabricated as thermal conductive but electric insulating filler for polymer matrix. Carbon fibers (CF) and MgO nanoparticles were firstly treated by the coupling agents with amine groups and epoxy groups, respectively. Then CFMgO was constructed through grafting the nanoparticles onto the surface of the fiber. It was expected that the thermal conductivity of CF would be enhanced but its electrical conductivity would be inhibited by the coating of MgO nanoparticles. The chemical structure and morphology of CFMgO were investigated using Fourier transform infrared spectrometer (FT-IR), X-ray photoelectron spectroscopy (XPS), and scanning electron microscope (SEM). Finally, the hybrid filler was introduced into Nylon 6. The strong interfacial interaction between the filler and matrix was exhibited, attributed to the existence of the coupling agents and the rough surface of nanoparticles-decorated CF. The highest thermal conductivity reached 0.748 W/m·K at 20 wt % addition of CFMgO. Meanwhile, the insulation of the composite appeared at higher than 10 wt% addition of the hybrid filler. Furthermore, connected by MgO nanoparticles, less CF was necessary for the construction of heat conduction channel, and lower value of percolation threshold was achieved.